Testosterone induction of prostaglandin-endoperoxide synthase 2 expression and prostaglandin F 2α production in hamster Leydig cells - Matzkin, María E. (2009)
We have previously observed expression of prostaglandin-endoperoxide synthase 2 (PTGS2), the key enzyme in the biosynthesis of prostaglandins (PGs), in reproductively active Syrian hamster Leydig cells, and reported an inhibitory role of PGF 2α on hamster testicular steroidogenesis. In this study, we further investigated PTGS2 expression in hamster Leydig cells during sexual development and photoperiodic gonadal regression. Since PTGS2 is mostly expressed in pubertal and reproductively active adult hamsters with high circulating levels of LH and androgens, we studied the role of these hormones in the regulation/maintenance of testicular PTGS2/PGF 2α. In active hamster Leydig cells, LH/hCG and testosterone induced PTGS2 and PGF 2α production, and their actions were abolished by the antiandrogen bicalutamide (Bi). These results indicate that LH does not exert a direct effect on PG synthesis. Testosterone also stimulated phosphorylation of the mitogen-activated protein kinase isoforms 3/1 (MAPK3/1) within minutes and hours, but the testosterone metabolite dihydrotestosterone had no effect on PTGS2 and MAPK3/1. Because Bi and U0126, an inhibitor of the MAP kinase kinases 1 and 2 (MAP2K1/2), abolished testosterone actions on MAPK3/1 and PTGS2, our studies suggest that testosterone directly induces PTGS2/PGF 2α in hamster Leydig cells via androgen receptors and a non-classical mechanism that involves MAPK3/1 activation. Since PGF 2α inhibits testosterone production, it might imply the existence of a regulatory loop that is setting a brake on steroidogenesis. Thus, the androgen environment might be crucial for the regulation of testicular PG production at least during sexual development and photoperiodic variations in hamsters.